2015
DOI: 10.1038/eye.2014.343
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic changes in systemic VEGF following intravitreal injections of ranibizumab in a child

Abstract: Purpose To investigate whether intravitreal ranibizumab injections administered to a child alter systemic plasma levels of total and free VEGF 165. Methods A 9-year-old child sustained a choroidal rupture from blunt trauma. He subsequently developed a secondary choroidal neovascular membrane, which was treated with five ranibizumab injections over a period of 8 months. Peripheral venous blood samples were taken at each visit over a period of 12 months and plasma was extracted. Plasma VEGF 165 levels were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…While bevacizumab was the most frequently used anti-VEGF agent at study locations 1 and 3, ranibizumab, bevacizumab and pegaptanib accounted for 40%, 40% and 20% of cases, respectively, receiving anti-VEGF treatment at study location 2. Ocular delivery of anti-VEGF agents has been shown to cause rapid and sustained systemic VEGF suppression in adult and paediatric patients 12. This has raised serious concerns, as VEGF is known to be vital in the development of major organs in children and the maintenance of normal organ function in adults 13.…”
Section: Discussionmentioning
confidence: 99%
“…While bevacizumab was the most frequently used anti-VEGF agent at study locations 1 and 3, ranibizumab, bevacizumab and pegaptanib accounted for 40%, 40% and 20% of cases, respectively, receiving anti-VEGF treatment at study location 2. Ocular delivery of anti-VEGF agents has been shown to cause rapid and sustained systemic VEGF suppression in adult and paediatric patients 12. This has raised serious concerns, as VEGF is known to be vital in the development of major organs in children and the maintenance of normal organ function in adults 13.…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al reported significant multiphasic changes of total and free plasma VEGF in a child following intravitreal ranibizumab injections. (19) As a result of two ranibizumab injections for DME, Gnanasekaran et al found an increase in VEGF levels in serum samples collected before and four weeks after administration. (20) Since this increase was seen only in the participants who received intravitreal injection, contrary to the hypothesis that hypoglycaemia induces the release of VEGF, it is more likely that this effect is due to an increase in VEGF synthesis, (21) and its release from the tissues into the circulation, (22) as mentioned in studies on cancer, which was the first field of use of anti-VEGF drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, small antibody molecules can be produced more economically and provide rapid biodistribution, which make them be potentially superior therapeutic molecules [12,13]. Several such small antibody molecules have been proved for the treatment of human diseases including ranibizumab (Fab, anti-VEGF), certolizumab(Fab, anti-TNF), blinatumomab (bispecific-scFv, anti-CD19/CD3) (www.fda.gov) or in clinical and preclinical development, such as scFv Efungumab, pexelizumab, DLX105, and Fab Digibind, abciximab, ranibizumab [14][15][16][17].…”
mentioning
confidence: 99%